Character Building of Students with Wise Use of Gadgets through Group Guidance Services - Wijayanah, Ade; Tobing, Christine Masada Hirashita; Saefudin, Dery Purnama (Asosiasi Asesmen Pendidikan (AAP), 2025)
The purpose of the study is to